Evaluation of Usability Based on User Satisfaction with the UI/UX Design of the E-Repository Prototype - Sabandar, Vederico Pitsalitz; Sintaro, Sanriomi (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
The user interface (UI) design of software in the early stages of development is crucial to ensure the future success of the product and is key to creating an effective user experience (UX). This study aims to produce a UI design for software, namely an e-repository, and conduct a usability evaluation based on user satisfaction with the UX of the design. The resulting e-repository design is a prototype, where the research process implemented the design thinking method consisting of five main phases: empathize, define, ideate, prototype, and test. The evaluation is conducted in the test phase, where the evaluation uses the usability testing method by assigning a number of task scenarios, totaling 8 tasks, to respondents. Furthermore, to measure user satisfaction levels, a questionnaire based on the System Usability Scale (SUS) is used, consisting of 10 statements with both positive and negative orientations. The research results indicate that the UI design has addressed the issues and met the needs of users. Meanwhile, the analysis results from the usability evaluation show that the Adjective Ratings are categorized as Good. Additionally, in terms of Acceptability Ranges, the prototype is deemed Acceptable by users, with a Grade Scale obtained being B, where the evaluation results indicate that the scores obtained are above the average SUS score standard.